ANALISIS YURIDIS KONSISTENSI PUTUSAN MAHKAMAH AGUNG DALAM KASUS MEREK YANG MENGANDUNG UNSUR PERSAMAAN PADA POKOKNYA (Putusan Pengadilan 2011-2012) - ELY YUSNITA (PREMISE LAW JURNAL, 2017)
A registered brand which product has been marketed should get protection according to Law No 15/2001 on Brand. In practice, many brands which are registered later, although it has similar basic elements, will be accepted its registration by the Directorate of Brand; this is contrary to Article 6, paragraphs 1, letters a, b, and c of Law No. 15/2001 on Brand. This thesis used legal normative and descriptive analytic method. Legal remedy can be made by the registered brand holder on the violation against his brand which has similar basic element based on Law No. 15/2001 by filing a complaint to the Court of Commerce on the withdrawal of the product with the brand which has similar basic element or by filing a compensation for the person who has registered the brand which has similar basic element. The Supreme Court’s Ruling in the dispute on a brand which has similar basic element in this research is not consistent toward legal protection against the registered brand. Keywords: Supreme Court’s Ruling, Similar basic Element